Pharmacokinetics and pharmacodynamics of diltiazem floating tablets - Gu Tian-Hua; Chen Shao-Xing; Zhu Jin-Bing; Song Dai-Jun; Guo Ji-Zhen; Hou Hui-Min (Acta Pharmacologica Sinica, 2016)
Floating tablet is a new type of delayed-action preparations. The present study was aimed at pharmacokinetic and hemodynamic effects of diltiazem floating tablet in 8 healthy volunteers. Each subject received po 90 mg diltiazem floating and normal tablets in a crossover design. For floating tablets the T1/2 (6.4 +/- 4.4 h) and Cmax (56 +/- 23 ng.ml-1) were longer and lower than those of normal tablets (2.3 +/- 1.1 h and 96 +/- 30 ng.ml-1, P < 0.01), respectively. AUC of the 2 forms were similar, suggesting that they had same bioavailability. Diltiazem lowered the blood pressure of the subjects. Although there was no significant difference between the 2 formulations in maximal decreases of systolic and diastolic blood pressures, the duration of hypotension was longer with floating tablets than that with normal ones. There was a positive correlation between diltiazem concentration and its hypotensive action. Thus, administration of floating tablets twice a day may be effective in controlling the blood pressure of hypertensive patients.